PENGARUH FREE CASH FLOW, HUTANG DAN TINGKAT PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Suherman, Robi; Lukman, Iing; Kusnadi, Kusnadi (Jurnal Manajemen Magister Darmajaya, 2015)
Dividend payout policy has an important impact for investors and for companies that pay dividends. Determination of the distribution of dividends becomes interesting problem because it will meet the expectations of investors, on the other hand the policy is not to inhibit the growth let alone threaten the survival of the company. The size of dividends to be paid by the company depending on the dividend policy of each company, so that management considerations are needed. It is thus necessary for the management to consider factors that influence dividend policy set by the company. The objective of research the effect of free cash flow, debt and the companys growth rate to dividend policy simultaneously and partially on manufacturing companies listed in Indonesia Stock Exchange (BEI). Samples are manufacturing companies with a total sample size of 6 companies. The analytical tool used is multiple linear regression analysis.Keyword: Dividend, Policy, Growth.